2016
DOI: 10.1007/s11001-016-9279-y
|View full text |Cite
|
Sign up to set email alerts
|

230Th/238U dating of hydrothermal sulfides from Duanqiao hydrothermal field, Southwest Indian Ridge

Abstract: Duanqiao hydrothermal field is located between the Indomed and Gallieni fracture zones at the central volcano, at 50°28 0 E in the ultraslow-spreading Southwest Indian Ridge (SWIR). Twenty-eight subsamples from a relict chimney and massive sulfides were dated using the 230 Th/ 238 U method. Four main episodes of hydrothermal activity were determined according to the restricted results: 68. 9-84.3, 43.9-48.4, 25.3-34.8, and 0.7-17.3 kyrs. Hydrothermal activity of Duanqiao probably started about 84.3 (±0.5) kyrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 62 publications
(79 reference statements)
1
16
0
Order By: Relevance
“…Two mineralisation stages were also recognised by previous researchers [26,27]. Similarly, ore samples recovered from the adjacent Duanqiao and Yuhuang hydrothermal fields also include Fe-rich relict sulphide talus or clasts (20V-S32-TVG14 and 21VII-S35-TVG22) consisting mostly of pyrite/marcasite with minor chalcopyrite and sphalerite ( Figure 2D,E), which might be derived from the recent collapse of inactive chimney edifices [24,29,80]. By contrast, the mineralisation style is somewhat unique at the Tianzuo field, which reflects complex ore-forming processes related to ultramafic-hosted hydrothermal environments of the ultraslow-spreading SWIR [86].…”
Section: Figuresupporting
confidence: 67%
See 2 more Smart Citations
“…Two mineralisation stages were also recognised by previous researchers [26,27]. Similarly, ore samples recovered from the adjacent Duanqiao and Yuhuang hydrothermal fields also include Fe-rich relict sulphide talus or clasts (20V-S32-TVG14 and 21VII-S35-TVG22) consisting mostly of pyrite/marcasite with minor chalcopyrite and sphalerite ( Figure 2D,E), which might be derived from the recent collapse of inactive chimney edifices [24,29,80]. By contrast, the mineralisation style is somewhat unique at the Tianzuo field, which reflects complex ore-forming processes related to ultramafic-hosted hydrothermal environments of the ultraslow-spreading SWIR [86].…”
Section: Figuresupporting
confidence: 67%
“…The Duanqiao (50.5 • E) field lies on an axial highland with a shallow depth of~1700 m. Seafloor morphology of the surrounding terrain is relatively flat [79]. Hydrothermal precipitates, including silica-rich metalliferous sediments (mostly amorphous opal), relict chimneys, and massive sulphide talus, are pervasive in this inactive field [23,80]. The Yuhuang (49.2 • E) field is situated on the south rift wall of segment 29, approximately 7.5 km from the ridge axis with a water depth ranging from 1400 to 1600 m. Its surrounding terrain exhibits NEE-striking highland features, with an elevation of~1500 m to the bottom of the rift valley [76].…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was not much related to rock debris or biological shells. Previous studies have revealed that Pb in massive sulfides from the Duanqiao Hydrothermal Field was chiefly leached from host rock (basalt), and the Pb contribution of seawater was negligible [19]. Through correlation analysis between Pb and HFSE and LILE (large ion lithophile element), in S25-21 plus S32-14ABC, r (Pb/Nb) = 0.427, r (Pb/Zr) = 0.012, r (Pb/Hf) = 0.056, r (Pb/Cs) = 0.872, r (Pb/Rb) = 0.616, and in S23-12, S17-4, S7-7 plus S37-21, r (Pb/Nb) = 0.880, r (Pb/Zr) = 0.008, r (Pb/Hf) = -0.019, r (Pb/Cs) = 0.259, r (Pb/Rb) = 0.437.…”
Section: Trace Element Geochemistry and Their Significancementioning
confidence: 99%
“…However, the hiatuses of almost 40kyrs from the inactive chimney collected in M zone, indicate venting continuous may not be integrated. Multi-stage of deposition have been reported widely for many conduits of the relict chimney samples (Wang et al, 2012;Yang et al, 2016).…”
Section: History Of the Hydrothermal Activities In Longqi-1 Fieldmentioning
confidence: 99%